Reframing Child Protection in Emergency Medicine - Joseph P. Shapiro; Genevieve Preer; Caroline J. Kistin (Western Journal of Emergency Medicine)
Child maltreatment remains a concerning source of morbidity and mortality in the United States, where more than 600,000 children are victims of abuse each year, with well-described, long-term consequences for physical and mental health. However, the US child welfare system is characterized by systemic racism and inequity. Black and Native American children are more likely to be evaluated and reported for suspected abuse despite evidence that race does not independently change their risk of being abused. Once reported to child protective services (CPS), these children are more likely to be removed from their homes and less likely to be reunited with their families than White children. Much of the inequity in this system starts at the front door, where a growing body of research demonstrates that bias regularly infiltrates decision-making in the initial clinical evaluation and management of suspected abuse. Minority children presenting to emergency departments (ED) are more likely to receive diagnostic testing and are more likely to be referred to CPS. In this editorial, we argue for the application of an equity lens to child protection in the ED. We discuss how emergency physicians can balance efforts to protect children from abuse with the imperative to protect children and families from the harms of an inequitable child welfare system. Our discussion concludes with concrete recommendations for emergency clinicians to participate in active bias mitigation and thoughtfully navigate their responsibilities as mandated reporters.